VD_FINDINFO HC / 2011 / 184 vom 11. April 2011 - VD Tribunal cantonal (2011)
EXÉCUTION FORCÉE, REJET DE LA DEMANDE, VICE DE PROCÉDURE | 502 al. 2 CPC, 309 let. a CPC (CH), 319 let. a CPC (CH), 320 CPC (CH), 339 al. 2 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)